Targeting amino acid metabolism to inhibit gastric cancer progression and promote anti-tumor immunity: a review - Jiang, Yuchun; Tao, Qing; Qiao, Xuehan; Yang, Yufei; Peng, Chen; Han, Miao; Dong, Kebin; Zhang, Wei; Xu, Min; Wang, Deqiang; Zhu, Wen; Li, Xiaoqin (Frontiers in Immunology, 2025)
The incidence of gastric cancer remains high and poses a serious threat to human health. Recent comprehensive investigations into amino acid metabolism and immune system components within the tumor microenvironment have elucidated the functional interactions between tumor cells, immune cells, and amino acid metabolism. This study reviews the characteristics of amino acid metabolism in gastric cancer, with a particular focus on the metabolism of methionine, cysteine, glutamic acid, serine, taurine, and other amino acids. It discusses the relationship between these metabolic processes, tumor development, and the body’s anti-tumor immunity, and analyzes the importance of targeting amino acid metabolism in gastric cancer for chemotherapy and immunotherapy.